APLIKASI MULSA Imperata cylindrica (L.), Mucuna bracteata DC. DAN KOMPOS PELEPAH KELAPA SAWIT (Elaeis guineensis Jacq.), TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN Mikania micrantha H.B.K. - Malinda, Sari; Fatonah, Siti; ', Herman (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The research on the use of mulch of Imperata cylindrica, Mucuna bracteata, and palm midrib compost on the germination and growth of Mikania micrantha had been conducted at the Laboratory of Biology and Botany Gardens, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Riau from September to November 2013. The purpose of this study was to determine the effect of mulch thickness of I. cylindrica, M. bracteata and palm midrib compost on the germination and growth of M. micrantha, using randomized block design, with seven treatments (M0, M1, M2, M3, M4, M5, and M6). Each treatment had seven replicates with two different thickness of mulch, i.e. 2,5 and 5 cm. The results showed that mulch of I. cylindrica, M. bracteata and palm midrib compost affected the germination and growth of weeds M. micrantha. Mulching with 2,5 cm thickness could inhibit the germination and growth of weed M. micrantha up to 100 %.